2015
DOI: 10.1039/c5nj01664a
|View full text |Cite
|
Sign up to set email alerts
|

A BODIPY/pyridine conjugate for reversible fluorescence detection of gold(iii) ions

Abstract: We designed a "turn-on" type fluorescent probe based a BODIPY-Pyridine conjugate which exhibits high selectivity towards Au(III) ions and, also responds to changes in the pH within the acidic pH range. The probe offers features such as rapid response time, a low detection limit, high sensitivity and selectivity. The detection of Au(III) is recognized by a distinct change in the emission intensity which relies on a reversible "ligand to ion" binding mechanism. We have also documented the utility of the probe fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Fluorescein hydrazide 1 and alkynyl benzaldehyde derivatives were refluxed in ethanol to give the title compounds, FL-1 and FL-2, in a yield of approximately 60%. The structures of both probes were also unambiguously confirmed by 1 H-NMR, 13 C NMR, and mass spectroscopy, as detailed in the Supporting Information (SI).…”
Section: Synthesis Of Fl-1 and Fl-2mentioning
confidence: 74%
See 2 more Smart Citations
“…Fluorescein hydrazide 1 and alkynyl benzaldehyde derivatives were refluxed in ethanol to give the title compounds, FL-1 and FL-2, in a yield of approximately 60%. The structures of both probes were also unambiguously confirmed by 1 H-NMR, 13 C NMR, and mass spectroscopy, as detailed in the Supporting Information (SI).…”
Section: Synthesis Of Fl-1 and Fl-2mentioning
confidence: 74%
“…FL-2 issued a highly similar fluorometric response to Au 3+ ions under the same sensing conditions. Moreover, treating FL-2 with Au 3+ selectively afforded FL-2P as the single product, as confirmed by 1 H NMR, 13 C NMR, and high-resolution mass spectroscopy analysis (S10 and S12, SI). The structure of the isolated product revealed that the receptor unit had undergone a highly selective endo-dig intramolecular cyclisation process to yield a sixmembered ring isoquinoline derivative.…”
Section: Reaction Mechanismmentioning
confidence: 88%
See 1 more Smart Citation
“…Compound 1 is bright, green fluorescent dye with similar excitation and emission to fluorescein with several uses in biochemistry, for staining lipids, membranes and other lipophilic compounds, because they exhibit narrow emission bandwidths, they have high extinction coefficient and fluorescence quantum yields and they are photostable. [1] Other applications of these dyes are related to fluorescent probes, [2][3][4] deep-red lighting sources, [5] bioactive CO-releasing molecules [6] and solar cells, [7] amongst many others. [8][9][10] Concerning BODIPY NMR properties, there are several compounds with reported data (Scheme 1) especially related to [11] ; 4, 1 J 11B19F = 33.4 Hz [12] ; 5, 11 B = 0.28, 1 J 11B19F = 28.7 Hz [13] ; 6, 11 B = 0.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 1 is bright, green fluorescent dye with similar excitation and emission to fluorescein with several uses in biochemistry, for staining lipids, membranes and other lipophilic compounds, because they exhibit narrow emission bandwidths, they have high extinction coefficient and fluorescence quantum yields and they are photostable . Other applications of these dyes are related to fluorescent probes, deep‐red lighting sources, bioactive CO‐releasing molecules and solar cells, amongst many others …”
Section: Introductionmentioning
confidence: 99%